Hubungan Status Kesehatan Ibu Saat Hamil dengan Kejadian Berat Badan Lahir Rendah (BBLR) - Hodijah, Alyah; Aisyah, Iis; Puspanditaning, Amanda (Jurnal Keperawatan Florence Nightingale, 2024)
Low birth weight (LBW) is a major health problem in Indonesia that can increase the prevalence of mortality and morbidity in infants. In 2022, the prevalence of LBW in Sumedang Regency showed an increase from 455 babies (2.54%) in 2021 to 509 babies (3.18%). The condition of LBW can occur due to maternal health disorders during pregnancy. The purpose of this study it to analyze the correlation between maternal health status and the incidence of LBW. The design used was analytical observational with participants mothers who gave birth at Sumedang Regional Hospital in 2022, with a total of 360 respondents. Based on the Chi Square Test result, there is a significant correlation between maternal health status and the incidence of LBW at Sumedang Regional Hospital with a P-value = 0.001. The conclusion of this study is that there is a correlation between maternal health status during pregnancy and the incidence of LBW, where multiple pregnancy has the greatest risk of giving birth to LBW babies. To maintain the pregnancy, pregnant women are advised to routinely carry out Antenatal Care (ANC).